Galvano- and thermo-magnetic effects at low and high temperatures within non-Markovian quantum Langevin approach - Abdurakhmanov, Ilkhom; Adamian, G.; Antonenko, N.; Kanokov, Z. (Elsevier BV * North-Holland, 2018)
© 2018 Elsevier B.V. The quantum Langevin formalism is used to study the charge carrier transport in a two-dimensional sample. The center of mass of charge carriers is visualized as a quantum particle, while an environment acts as a heat bath coupled to it through the particle–phonon interaction. The dynamics of the charge carriers is limited by the average collision time which takes effectively into account the two-body effects. The functional dependencies of particle–phonon interaction and average collision time on the temperature and magnetic field are phenomenologically treated. The galvano-magnetic and thermo-magnetic effects in the quantum system appear as the results of the transitional processes at low temperatures.